The Application of Value Management on Real Estate Development Case Study: Developers in Surabaya - Sari, Yeptadian (International Journal of Built Environment and Scientific Research, 2017)
The application of a method in real estate development process is needed in order to ensure the project runs smoothly. There are methods that can increase the value of the project and even discard unnecessary cost of the project called value management. Many practitioners of real estate development in Surabaya claim that they always apply value management method. However, based on empirical data, it is known that not much research of value management in Surabaya. The purpose of this paper are to determine how the application of value management by developers of real estate development in Surabaya and when the right stage is to execute that method. Statistic descriptive analysis is used to achieve the research objectives. Results of research in this paper are the perception of value management by developers in Surabaya and real estate development stage in which value management method commonly executed in Surabaya.Â